EXAMINATION OF THE DEVELOPMENT AND SCHOOL READINESS OF PRE-SCHOOL AGE CHILDREN (4-6 YEARS) AS PREPARATION FOR ENTERING PRIMARY SCHOOL - Azizah, Nurona; Amaliya, Sholihatul; Kapti, Rinik Eko; Fadhila, Putri Nur; Novarani, Nabila; Nabilla, Mega Wahyu (Caring: Jurnal Pengabdian Masyarakat, 2024)
Growth screening examinations are essential to assess whether a child is ready to enter a more structured education system because they can determine success at the formal education level. Our service was carried out by three service teams: eleven students from the Nursing Dept., Universitas Brawijaya, and eleven pre-school teachers. This activity is carried out from October to November 2023. We aimed to observe how children's nutrition status from height and weight (1), observe children's developmental checks using the Pre-Developmental Screening Questionnaire (KPSP) instrument (2) and discuss with parents the results of the child's growth and development health screening (3). The total number of children who could be observed was 97 children. The activity results showed that 49 children were female (51%) and 48 children were male (49%). The age range was 47-81 months, with the average age being five years. The growth results showed that 67 children were normal, and 10 were underweight (thin). There are no fat children. For height, 71 children were of normal height, 20 children were classified as tall, five children were classified as short, and one child had stunting. The development results using the pre-development screening questionnaire (KPSP) were that 71 children had appropriate development, 16 children had questionable development, and 10 children had development deviations. Most failures in development occurred in the language sector. This service is also conducted through consultation between lecturers and parents and provides information parents need for their child's school readiness. Hopefully, these results can be used as considerations for parents to determine when their children will start elementary school.